Instrumentation for engineering measurements - Dally, James W. (John Wiley and Sons, 1993)
This book is about: Applications of electronic instrument systems; Analysis of circuits; Analog recording instruments; Digital recording systems; Sensors for transducers; Signal conditioning circuits; ...